Pengaruh Kepemimpinan Transformasional, Komitmen Organisasional, dan Kualitas Kehidupan Kerja terhadap OCB pada FIFGROUP Sleman 1 - Elgi Trans Aditya Surbakti; Kusuma Chandra Kirana; Tri Ratna Purnamarini (SAFE-Network, 2026)
This investigation was undertaken to scrutinize the degree to which transformational leadership, organizational commitment, and quality of work life collectively shape the manifestation of Organizational Citizenship Behavior (OCB) among the workforce of PT FIFGROUP Sleman 1, Yogyakarta. OCB is conceptualized as discretionary conduct that emerges organically from employees, transcending their prescribed duties and yielding constructive outcomes for the broader organizational system. This investigation adopted a quantitative paradigm, encompassing the entire employee population as participants via a census-based sampling procedure. Primary data were gathered through a structured Likert-scaled instrument and subsequently subjected to multiple linear regression analysis utilizing SPSS computational software. Each measurement instrument demonstrated conformity with the requisite psychometric benchmarks of validity and reliability assessment. Analytical outcomes disclosed that transformational leadership failed to yield a statistically discernible effect on employee OCB. Conversely, organizational commitment exhibited a pronounced and affirmative influence on the surfacing of OCB among respondents. Notably, quality of work life distinguished itself as the predominant determinant within the examined set of predictors. In aggregate, the three predictors accounted for roughly one-third of the observable variance in OCB across the organizational setting. Drawing from these outcomes, organizational leadership is encouraged to concentrate on elevating work-life quality and consolidating employee dedication as the foundational pillars for cultivating enduring OCB tendencies.